Burkholderia cenocepacia in cystic fibrosis: epidemiology and molecular mechanisms of virulence - Drevinek, P; Mahenthiralingam, E (Clinical microbiology and infection, 2010)
Burkholderia cepacia complex (Bcc) bacteria have gained notoriety as pathogens in cystic fibrosis (CF) because they are difficult to identify and treat, and also have the ability to spread between CF individuals. Of the 17 formally named species within the complex, Burkholderia multivorans and Burkholderia cenocepacia dominate in CF. Multilocus sequence typing has proven to be a very useful tool for tracing the global epidemiology of Bcc bacteria and has shown that B. cenocepacia strains with high transmissibility, such as the ET-12 strain (ST-28) and the Czech strain (ST-32), have spread epidemically within CF populations in Canada and Europe. The majority of research on the molecular pathogenesis of Bcc bacteria has focused on the B. cenocepacia ET-12 epidemic lineage, with gene mutation, genome sequence analysis and, most recently, global gene expression studies shedding considerable light on the virulence and antimicrobial resistance of this pathogen. These studies demonstrate that the ability of B. cenocepacia to acquire foreign DNA (genomic islands, insertion sequences and other mobile elements), regulate gene expression via quorum sensing, compete for iron during infection, and mediate antimicrobial resistance and inflammation via its membrane and surface polysaccharides are key features that underpin the virulence of different strains. With the wealth of molecular knowledge acquired in the last decade on B. cenocepacia strains, we are now in a much better position to develop strategies for the treatment of pathogenic colonization with Bcc and to answer key questions on pathogenesis concerning, for example, the factors that trigger the rapid clinical decline in CF patients.
Keywords: molekulární epidemiologie; bakteriální léková rezistence; Drug Resistance, Bacterial; Canada; Respiratory Tract Infections; Europe; rozptýlené repetitivní sekvence; virulence; Evropa; Kanada; Quorum Sensing; mutace; Burkholderia Infections; Burkholderia cenocepacia; Cystic Fibrosis; Multilocus Sequence Typing; Gene Expression; Mutation; Virulence; Humans; Molecular Epidemiology; quorum sensing; bakteriální polysacharidy; Burkholderia cepacia complex; exprese genu; Burkholderia cepacia komplex; multilokusová sekvenční typizace; infekce dýchací soustavy; Polysaccharides, Bacterial; lidé; cystická fibróza; Interspersed Repetitive Sequences; infekce bakteriemi rodu Burkholderia